P061 Circulating inflammatory protein and cellular profiles at time of diagnosis classify inflammatory bowel disease patients according to their underlying immune response and clinical disease course. (21st January 2022) - Heredia, M; Charrout, M; Klomberg, R C W; Aardoom, M A; Jongsma, M M E; Kemos, P; van Haaften, D H; Tuk, B; van Berkel, L A; Bley Folly, B; Mahfouz, A; Reinders, M J T; et al.
Abstract: Background: Chronicity of inflammatory bowel disease (IBD) is driven by reactivation of inflammatory memory CD4 + T helper (Th) cells which activate an inflammatory cascade involving innate immune cells and structural intestinal tissue cells. Because of disease heterogeneity, novel treatment strategies tailored to more precisely target the patient's individual immune defect are required to prevent disease reactivation. We hypothesize that analysis of changes in circulating inflammatory protein abundance combined with phenotyping of circulating Th cells allow to dissect underlying immune pathogenesis and aim to stratify pediatric IBD patients accordingly. Methods: We performed plasma analysis of 92 inflammatory proteins in a cohort of pediatric IBD patients (CD: n=62; UC/IBD-U: n=20), patients with suspicion of IBD but negative diagnosis (n=13) and age-matched healthy controls (HC: n=30). Peripheral blood was obtained at diagnosis and after induction treatment (t=10–14 weeks). Plasma protein concentrations were assessed with Olink Proximity Extension Assay technology® and Th cells were analyzed with flow cytometry. Results: Thirty-six plasma proteins discriminated pediatric IBD patients from HC. CD and UC/IBD-U patients shared increased abundance of 17 proteins amongst which interleukin-6 and oncostatin-M. Increased abundance of the Th1 cytokine interferon-γ was strictly associated with CD while Th17-associated interleukin-17A was significantly more abundant in UC/IBD-U. Hierarchical clustering of plasma protein profiles discriminated 2 clusters of UC patients with different clinical disease activity and disease extent. In CD, three patient clusters were identified. CD#3 patients had lower clinical disease activity, lower C-reactive protein and higher blood albumin concentrations, while clusters CD#1 and CD#2 had comparable clinical parameters. CD#1 patients had higher abundance of 14 proteins associated with neutrophil function and interferon-γ signaling while CD#2 patients had a marked increase in frequencies of activated (HLA-DR + ) memory Th cells. The three CD clusters responded differently to therapy with CD#1 patients exhibiting more modulated proteins and greater fold changes, CD#2 patients showing intermediate modulation and CD#3 patients exhibiting only a few changes. Conclusion: Combined plasma immune protein and circulating Th cell profiling combined with in depth clinical monitoring discriminates subgroups of pediatric IBD patients during active disease which differ in their response to induction therapy. Abbreviations: CD: Crohn's disease; UC: ulcerative colitis; IBD-U: IBD-unclassified.